Photosensitization of nanoparticulate TiO2 using a Re(I)-polypyridyl complex: studies on interfacial electron transfer in the ultrafast time domain - Kar, Prasenjit; Banerjee, Tanmay; Verma, Sandeep; Sen, Anik; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra N. (Physical Chemistry Chemical Physics, 2012)
We have synthesized a new photoactive rhenium(I)-complex having a pendant catechol functionality [Re(CO)3Cl(L)] (1) (L is 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) for studying the dynamics of the interfacial electron transfer between nanoparticulate TiO2 and the photoexcited states of this Re(I)-complex using femtosecond transient absorption spectroscopy. Our steady state absorption studies revealed that complex 1 can bind strongly to TiO2 surfaces through the catechol functionality with the formation of a charge transfer (CT) complex, which has been confirmed by the appearance of a new red-shifted CT band. The longer wavelength absorption band for 1, bound to TiO2 through the proposed catecholate functionality, could also be explained based on the DFT calculations. Dynamics of the interfacial electron transfer between 1 and TiO2 nanoparticles was investigated by studying kinetics at various wavelengths in the visible and near infrared regions. Electron injection into the conduction band of the nanoparticulate TiO2 was confirmed by detection of the conduction band electron in TiO2 (Image ID:c2cp24105f-t1.gif) and the cation radical of the adsorbed dye (1˙+) in real time as monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (<100 fs) electron injection was observed. Back electron transfer dynamics was determined by monitoring the decay kinetics of 1˙+ and Image ID:c2cp24105f-t2.gif.

Design of efficient metal-free organic dyes having an azacyclazine scaffold as the donor fragment for dye-sensitized solar cells - Biswas, Abul Kalam; Barik, Sunirmal; Sen, Anik; Das, Amitava; Ganguly, Bishwajit (Journal of Physical Chemistry C, 2014)
The energy conversion efficiency of dye-sensitized solar cells derived from organic dye molecules has seen immense interest recently. In this work, we report a series of organic donor molecules with enhanced energy conversion efficiency using ?-spacers and cyanoacrylic acid as an anchoring group (2-6). Density functional theory (DFT) and time-dependent DFT calculations of these molecules have been performed to examine their electronic structures and absorption spectra before and after binding to the semiconductor titanium dioxide surface. The computational results suggest that dyes 4 and 6 have a larger driving force (Delta G(inject) = -1.66 and -1.80 eV, respectively) and light-harvesting efficiency (LHE = 0.99) in the series of donor molecules studied. Thus, these dyes should possess a larger short-circuit photocurrent density (J(sc)) compared to the other examined dyes. The reported Delta G(inject) (-1.62 eV) and LHE (0.98) for compound 1, calculated with the same level of theory, were lower than those of the designed 4 and 6 dyes. Furthermore, the DFT calculations showed that the open-circuit photovoltage (V-oc) is improved with the vertical dipole moment and number of photoinjected electrons for 4 and 6. Dyes 4 and 6 are expected to exhibit high solar-energy-to-electricity conversion.